EFEKTIVITAS METODE TALAQQI DALAM MENINGKATKAN HAFALAN AL-QUR’AN ANAK USIA DINI DI RAUDHATUL ATHFAL AMANAH UMMAH SURAKARTA - Hartati, Sri; Halimah, Nadiya; Sulistyani, Utami; Abbas, Ngatmin (STKIP Pesisir Selatan, 2025)
The central research question addressed is: To what extent does the talaqqi method influence the improvement in both the quality and quantity of Qur’anic memorization in early childhood learners? This research adopts a qualitative case study approach, complemented by quantitative data through pretest and posttest assessments. Data were collected through participatory observation, in-depth interviews with teachers, school leaders, and parents, documentation of daily activities, and memorization tests to measure student achievement. The findings indicate that the talaqqi method, conducted daily through stages of listening, imitating, and repeating Qur’anic verses, is significantly effective in enhancing students’ memorization abilities. On average, students demonstrated an increase of 8 to 9 verses within a four-week period. Indirect impacts were also observed, such as improved discipline, greater love for the Qur’an, and respectful behavior during the learning process. This study contributes practical insights for developing effective tahfidz strategies in Islamic early childhood education and recommends future development of the talaqqi method through the integration of audio-visual media and play-based approaches. The findings highlight the importance of embedding Qur’anic values holistically in early childhood Islamic education.